Peran PPAT Dalam Melakukan Pengecekan Sertifikat Secara Elektronik Pada Perjanjian Jual Beli Tanah - Maharani, Desak Komang Lina; Westra, I Ketut (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 02 (2022), 2022)
The purpose of writing is to increase knowledge about PPAT's responsibility for discrepancies in the results of checking certificates electronically as well as efforts to resolve discrepancies in results of checking certificates electronically. This writing uses a normative legal research method by reviewing regulations related to the role of PPAT in checking electronic certificates in land sale and purchase agreements, by applying the statutory approach, and the conceptual approach, as well as using primary, secondary and legal materials. tertiary and then the results are described descriptively. The results of the study show that the responsibility of the PPAT who is directly involved in the electronic certificate checking process is to ensure that the data, both juridical data and physical data on the results of electronic certificate checking, are in accordance with the original certificate. Efforts that can be made by PPAT if there is a data discrepancy, then PPAT sends a notification through the relevant information service system so that the inconsistent data is immediately updated or by visiting the BPN office, bringing proof of the results of checking the electronic certificate that has been printed and the original certificate. Then the BPN will provide information by updating the data on the system.